Guía didáctica para motivar el control de la contaminación del suelo por depósitos de ácidos, en los estudiantes del tercer año de bachillerato, del paralelo a, de la unidad educativa Dr. Manuel Agustín Cabrera Lozano” de la ciudad de Loja, período 2014 – 2015. - Troya Tamayo, Maykel Alcivar (2017)
In the teaching-learning process different methodologies are used, such as: training and awareness, these are important components in soil pollution prevention programs. Current education requires that teachers use methodological strategies to motivate students in such a way that the teaching-learning process is improved. In the present investigation through the application of the Didactic Guide, it is hoped to contribute to achieve meaningful learning, in order to motivate, guide and strengthen the daily activities of teachers and students in the teaching-learning process. To do this, students must be motivated to reduce soil pollution, through prevention programs, using didactic technology such as: television programs, educational videos, and blogs. So students are motivated by the learning of soil contamination by acid deposits. In general the Didactic Guide is an educational material to help motivate and evaluate the teaching-learning process in students. In this context, the present research aims to develop a DIDACTIC GUIDE TO MOTIVATE THE CONTROL OF SOIL CONTAMINATION BY ACID DEPOSITS, IN THE STUDENTS OF THE THIRD YEAR OF BACHILLERATO, OF THE PARALLEL "A", OF THE EDUCATIONAL UNIT "DR. MANUEL AGUSTÍN CABRERA LOZANO "FROM THE CITY OF LOJA, PERIOD 2014-2015. It was formulated as a general objective: To develop the Didactic Guide as a methodological strategy to motivate the control of soil contamination by acid deposits, with students of third year of Parallel Baccalaureate "A", from the Educational Unit "Dr. Manuel Agustín Cabrera Lozano "of the city of Loja, period 2014 - 2015. The methods used were: analytical-synthetic, inductive-deductive, descriptive and bibliographical, which served to interpret data gradually from sources; Such as books, web pages, magazines, and reliable documents. As technique was applied: the survey and how (questionnaire instrument); in addition the method of linear correlation of Pearson through the application of the pre-test and post-test. As sample was taken 28 students and 1 teacher of the institution, object of investigation. After the present investigation, the results indicate that the students to develop their academic activities in the teaching-learning process do not know about the contamination of the soil by acid deposits, proving in this way that the level of knowledge in relation to the contamination of the soil is limited. Therefore it is necessary to use a Didactic Guide to motivate the control of soil contamination by acid deposits, as a didactic alternative for the revision of these contents.